Graphene oxide and reduced graphene oxide promote the effects of exogenous T3 thyroid hormone in the amphibian Xenopus laevis. (October 2021) - Evariste, Lauris; Mottier, Antoine; Pinelli, Eric; Flahaut, Emmanuel; Gauthier, Laury; Mouchet, Florence
Abstract: The interest for graphene-based nanomaterials (GBMs) is growing worldwide as their properties allow the development of new innovative applications. In parallel, concerns are increasing about their potential adverse effects on the environment are increasing. The available data concerning the potential risk associated to exposure of aquatic organisms to these GBMs are still limited and little is known regarding their endocrine disruption potential. In the present study, the endocrine disruption potential of graphene oxide (GO) and reduced graphene oxide (rGO) was assessed using a T3-induced amphibian metamorphosis assay. The results indicated that GBMs potentiate the effects of exogenous T3 with a more marked effect of GO compared to rGO. T3 quantifications in the exposure media indicated adsorption of the hormone on GBMs, increasing its bioavailability for organisms because GBMs are accumulated in the gut and the gills of these amphibians. This study highlights that the tested GBMs do not disrupt the thyroid pathway in amphibians but indicates that adsorption properties of these nanomaterials may increase the bioavailability and the toxicity of other pollutants. Graphical abstract: Image 1 Highlights: GO and rGO promote effects of exogenous T3 in Xenopus laevis model. T3 effects were more marked in presence of GO than in presence of rGO. GBMs accumulated by the tadpoles adsorb T3 hormone and improve its bioavailability. T3 effects are promoted by graphene oxide and reduced graphene oxide in head areas. GO and rGO do not exert direct endocrine disruption towards amphibians.